Idiopathic, bilateral panuveitis – efficacy of general steroidotherapy and intravitreal dexamethason injection. Case report - Zygmunt, Hanna; Raczyńska, Krystyna; Czuszyński, Witold (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
This paper presents the comparison of different schemes of two kinds of general steroidotherapy in one case of idiopathic, bilateral panuveitis and effectiveness of intravitreal dexamethason to one eye. The effectiveness of the treatment was mainly concerned on best corrected visual acuity, the illustration of macular retinal area in OCT (optic coherence tomography), where the reduction of cystic macular oedema was detected and the pictures of fluorescein angiography. The observation and the treatment has lasted for 3 years. At the beginning, the patient received general steroidotherapy (medrol), which lasted seventy four days. Improvement of clinical symptoms lasted only four months. The similar therapy the patient obtained once more. The symptoms of illness returned, after the same period of time. Then the intravitreal dexamethason (Posurdex) was injected. The better visual acuity and improvement of clinical symptoms was observed for three months. The patient couldn’t obtain posurdex once more. The physician decided to apply the different scheme of general steroidotherapy. The observation after finished treatment, lasted over one year. Clinical symptoms of the illness retracted. The fluorescein angiography of the eyes were correct and the structure of the macular retinal area presented in optical coherence tomography were regular. The observation of the patient is continued.